2019
DOI: 10.1016/j.bbrep.2018.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Streptavidin cooperative allosterism upon binding biotin observed by differential changes in intrinsic fluorescence

Abstract: While the binding of biotin by streptavidin does not appear to be cooperative in the traditional sense of altered binding strength, it has been suggested that it may be cooperative in terms of differential structural changes in the protein. In this work we present intrinsic tryptophan fluorescence data as evidence of a cooperative structural change. The technique involves examination of the differences in fluorescence emission corresponding to distinct tryptophan populations accompanying protein-ligand binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 25 publications
6
17
0
Order By: Relevance
“…8e). Although a previous study indicated that the binding of biotin is not cooperative according to principal component analysis 44 , these results confirm that biotin binding may not have a stabilizing effect but can cause the allosteric response of streptavidin 23 . Also, biotin binding may affect other dimer chains of the tetrameric structure and provide cooperativity for additional ligand binding by perturbing active site residues.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…8e). Although a previous study indicated that the binding of biotin is not cooperative according to principal component analysis 44 , these results confirm that biotin binding may not have a stabilizing effect but can cause the allosteric response of streptavidin 23 . Also, biotin binding may affect other dimer chains of the tetrameric structure and provide cooperativity for additional ligand binding by perturbing active site residues.…”
Section: Discussionmentioning
confidence: 48%
“…Our data suggest that this structural feature is intermolecular allostery between monomers of streptavidin. Recently, a new model was proposed to describe structural cooperativity of streptavidin and a cooperative allosterism upon binding biotin 23 . Ligand binding is characterized by L3/4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8e) . Although a previous study indicated that the binding of biotin is not cooperative according to PCA analysis [44], these results confirm biotin binding may not have a stabilizing effect but can cause the allosteric response of streptavidin [23]. Also, biotin binding may affect other dimer chains of the tetrameric structure and provide cooperativity for additional ligand binding by perturbing active site residues.…”
Section: Discussionmentioning
confidence: 67%
“…Along with two opposing views, it was also suggested that the streptavidin-biotin interaction showed positive cooperativity, and the cooperativity of the tetramer was accompanied by closeness of the streptavidin upon biotin-binding [21,22]. Later on, this phenomenon was named "cooperative allosterism" [23]. Streptavidin-biotin complex has numerous applications and many of them are investigated structurally.…”
Section: Introductionmentioning
confidence: 99%